2017
DOI: 10.1371/journal.pone.0185751
|View full text |Cite
|
Sign up to set email alerts
|

Military service, deployments, and exposures in relation to amyotrophic lateral sclerosis survival

Abstract: BackgroundMilitary veterans may have higher rates of amyotrophic lateral sclerosis (ALS) mortality than non-veterans. Few studies, with sparse exposure information and mixed results, have studied relationships between military-related factors and ALS survival. We evaluated associations between military-related factors and ALS survival among U.S. military veteran cases.MethodsWe followed 616 medical record-confirmed cases from enrollment (2005–2010) in the Genes and Environmental Exposures in Veterans with Amyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…A Legionella -ALS hypothesis is supported by similarities in the descriptive epidemiology of Legionnaires’ disease and ALS: the peak incidence of both diseases occurs after age 50 years; both show a male predominance; and the only established behavioral risk factor for ALS, cigarette smoking, is a risk factor for infection with Legionella (63). Military veterans appear to have an increased risk for ALS, regardless of deployment status (64). That finding is intelligible because hospitalization for pneumonia, including that caused by Legionella , is many times more common in recruit than in civilian populations (65,66).…”
Section: Discussionmentioning
confidence: 99%
“…A Legionella -ALS hypothesis is supported by similarities in the descriptive epidemiology of Legionnaires’ disease and ALS: the peak incidence of both diseases occurs after age 50 years; both show a male predominance; and the only established behavioral risk factor for ALS, cigarette smoking, is a risk factor for infection with Legionella (63). Military veterans appear to have an increased risk for ALS, regardless of deployment status (64). That finding is intelligible because hospitalization for pneumonia, including that caused by Legionella , is many times more common in recruit than in civilian populations (65,66).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 A lower bound for the genetic contribution is given by the proportion of variance associated with common single-nucleotide polymorphisms (SNPs) genome-wide, the SNP-based heritability estimated as 8.5% (CI 95% = [7.5-9.5]) in Europeans 3 and 15% (CI 95% = [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]) in East Asians. 4 Epidemiological studies have also identified environmental and occupational risk factors, such as metal and pesticide exposure 5 and defense force occupation, 6,7 but generally studies are underpowered. 8 Hence, lifetime environmental exposures paired with genetic susceptibility likely contribute to an increased risk for ALS.…”
Section: Introductionmentioning
confidence: 99%
“…5 Brain Center Rudolf Magnus, University Medical Center Utrecht, Utrecht 3584 CG, Netherlands. 6 Mater Research Institute, The University of Queensland, Brisbane, QLD 4101, Australia. 7 Queensland Brain Institute, The University of Queensland, Brisbane, QLD 4072, Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10% of ALS cases are classified as familial ALS, in which the disorder tends to be inherited in an autosomal dominant fashion (16,40), and numerous contributory genes have been identified (1). Other risk factors for the development of ALS include age (6), male gender (16) and military service (7,38,43,50,88). Despite differences in etiology, sporadic and familial ALS possess similar patterns of neuropathological degeneration (2).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have noted that 50% of patients die within the first 3 years after disease onset, and only a small fraction of cases (~10%) survive 10 years or longer (24,63,74). Furthermore, large database and population-based studies have reported the median death in the US and Europe as approximately 3 years after disease onset (7,41,44,73). Previous studies have shown most cases of ALS have survival rates of less than 10 years and suggest that patients with ALS that survive 10 years or more represent a group with altered biology (23,87).…”
Section: Introductionmentioning
confidence: 99%